Dosing Patterns during Conversion to IPX066, Extended-Release Carbidopa-Levodopa (ER CD-LD), in Parkinson’s Disease with Motor Fluctuations - John C. Morgan; Rohit Dhall; Robert Rubens; Sarita Khanna; Suneel Gupta (Parkinson's Disease)
Background. IPX066 is an extended-release (ER) oral formulation of carbidopa-levodopa (CD-LD). Following an initial peak at about one hour, plasma LD concentrations are maintained for about 4-5 hours. Objective. To present dosing factors that may affect the successful conversion to ER CD-LD from other LD formulations. Methods. Two-phase 3 studies of ER CD-LD vs. immediate-release (IR) CD-LD (ADVANCE-PD) and vs. CD-LD + entacapone (CLE; ASCEND-PD) in subjects with advanced PD included a 6-week, open-label conversion to ER CD-LD prior to treatment randomization. The “converted” daily LD dose ratio and dose frequency for ER CD-LD were compared to the prior LD treatment regimens at study entry. Results. The average daily LD dose ratio at the end of dose conversion to ER CD-LD was approximately 2.1 for IR CD-LD and 2.8 for CLE. The final dose ratios tended to be slightly higher for participants taking lower LD doses at study entry but independent of dose frequency. ER CD-LD dose frequency increased with increasing LD dose and dose frequency at study entry. Participants on higher baseline LD doses ≥800 mg and dose frequencies ≥6 tended to have higher rates of discontinuation during conversion to ER CD-LD. Conclusions. Converting participants from other LD formulations to ER CD-LD is based on their current LD regimen. For the most common daily doses (≤1250 mg) and dose frequencies (<7) of LD, final mean dose ratios were within tight ranges of 2.1 to 2.4 for IR CD-LD (ADVANCE-PD) and 2.4 to 2.8 for CLE (ASCEND-PD) and were generally independent of the LD dosing frequency at study entry. These trials are registered with NCT00974974, NCT01130493.